Profil Industri Kecil Tekstil dan Produk Tekstil (TPT) di Kabupaten Klaten - Nur Feriyanto (Economic Journal of Emerging Markets, 2004)
This research analyses the profile of small-scale industries of textile and its pro¬ducts (TPT) in Klaten. There are five aspects analyzed i.e. business, financial, government support, management and institutional. The result shows that TPT industries are potential enough to be developed in order to increase the economy growth. The development will also benefit for creating new employment, increasing in production, and marketing the product both locally and internationally.Keywords: profile, textile, small-scale industry.